Anterior vestibule salvaging technique to limit silicone orbital implant extrusion following evisceration. (4th July 2019) - Moore, Nicholas A.; Fu, Roxana; Clark, Jeremy; Prendes, Mark; Nunery, William R.; Burgett, Richard A.; Lee, H.B. Harold
ABSTRACT: Purpose : The anterior vestibule salvaging ('Birdcage') technique may limit orbital implant extrusion following evisceration. Methods : A 10-year retrospective chart review from 2005 to 2015 of individuals who underwent evisceration procedures utilizing the vestibule salvaging technique was performed. Results : A total of 96 patients (61 male; 35 female; average age 64 years; range 17–96 years) underwent evisceration with a technique avoiding anterior scleral relaxing incisions. Three (3.1%) patients had documented extrusion of the silicone implant. Time from evisceration to extrusion ranged from 26 to 372 days. Conclusions : Maintenance of the anterior scleral vestibule during evisceration may decrease extrusion rates after surgery compared with traditional evisceration techniques that utilize anterior relaxing incisions.